Coaching Process Of Prisoners In Correctional Institution Class I Kedungpane Semarang Viewed From Act No 12 Of 1995 On Concerning The Correctional Institution - Antoni Muhamad Nur Cahyo; Achmad Sulchan (Jurnal Daulat Hukum, 2020)
The problem this study are: a) how the coaching process in prison inmates Class 1 Kedungpane Semarang in terms of Act No. 12 of 1995 on Correctional Institution? and b) whether a limiting factor in the implementation of prison inmate gave coaching in the Correctional Institution Class I Kedungpane Semarang? Researchers using normative juridical approach. The source and type of data in this study are primary data obtained from field studies with interviews at the Correctional Institution Class I Kedungpane Semarang. And secondary data obtained from the study of literature. Based on the results of the implementation study coaching in the penal system for prisoners gradually form has been going well, the first stage of the introduction of the orientation stage where inmates including receiving prisoners, registration inmates and temporary placement of prisoners, the introduction of a maximum of 1 month. The second stage of assimilation in the strict sense lasts from 1/3 to 1/2. The third stage is the stage of assimilation in a broader sense and has lived half of a criminal past. The fourth stage is the stage of integration with the community has undergone criminal or 2/3 of the time for at least 9 months. The obstacles that occur due to the lack of Correctional officer training, infrastructure is still lacking adequate. Addition of facilities are still related to education problem such as library books, any additional school, socializing with new science and training tools. Construction of shelter / blocks apart to make it more comfortable for them.Keywords: Correctional Institution; Prisoners; Development.